Political theology of international order - Bain, William (Oxford University Press, 2020)
Order and theology -- Rival conceptions of order : immanent and imposed -- Renaissance, reformation, and the road to Westphalia -- Martin Luther and the theology of the two kingdoms -- Hugo Grotius and the God of international society -- Thomas Hobbes and the divine politics of Anarchy -- Political theology I : system, anarchy, balance of power -- Political theology II : society, law, constitution -- International order beneath an empty sky.